A Study Of Ambiguity In The Articles Of "Life & Times" Column In The Jakarta Globe Newspaper - Maharani, Ikha Muflikhah (2012)
The research deals with the ambiguity which is reflected in the articles of Life & Times column in the Jakarta Globe newspaper. The aims of the research are (1) to describe what the types of ambiguity, (2) to describe the dominant ambiguity, and (3) to describe the reasons of the ambiguous sentences. The type of this research is descriptive qualitative research. The data source of this research is headline news articles of Life & Times column in the Jakarta Globe newspaper in Desember 2011. The data collection technique is documentation. The technique of data analysis are having a list of ambiguous sentences, describing the types of ambiguity and describing the ways to disambiguate those sentences. The writer uses the theories of Kent Bach, Trask and Stockwell, and Kempson to analyze the types of ambiguity. The results of the study show that (1) the writer finds all the types of ambiguity namely: lexical ambiguity and structural ambiguity, (2) the dominant types of ambiguity is structural ambiguity, and (3) the two main sources of the reasons of ambiguous sentence are word order and word meaning. The frequency of each type of ambiguity are: (1) Structural ambiguity with 15 surface structure ambiguity or 37, 5 % and 13 deep structure ambiguity or 32, 5 %, and (2) Lexical ambiguity with 12 number of ambiguous sentences or 30 %.